A new Agraecina spider species from the Balkan Peninsula (FYR Macedonia) (Araneae: Liocranidae) - Deltshev, Christo; Wang, Chunxia (Zootaxa, 2016)
Specimens were collected using pitfall traps. Coloration is described from alcohol-preserved specimens. Specimens were examined and measured using a Wild M5A stereomicroscope. Further details were studied and measured under an Olympus BX41 compound microscope. All drawings were made using a drawing apparatus attached to a Leica stereomicroscope. Male palps and female genitalia were examined and illustrated after they were dissected from the spiders’ bodies. Photos were taken with an Olympus C7070 wide zoom digital camera mounted on an Olympus SZX12 stereomicroscope. The images were montaged using Helicon Focus image stacking software. Measurements of the legs are taken from the dorsal side. Total length of the body includes the chelicerae. All measurements were taken in mm. Abbreviations used in text include: AME, anterior median eyes; ALE, anterior lateral eyes; EM, embolus; MA, median apophysis; CD, copulatory duct; ST, spermatheca; fe, femur; pa, patella; ti, tibia; mt, metatarsus; p, prolateral; d, dorsal; r, retrolateral; v, ventral. Type specimens are deposited in the National Museum of Natural History (NMNHS), Sofia, Bulgaria.